การพัฒนาทักษะการอ่านออกเสียงคำในภาษาไทยของนักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนศรีธรรมวิทยา ตำบลในเมือง อำเภอเมือง จังหวัดยโสธร - วงศ์น้ำคำ, กัณฐิกา; ดร., พระครูประสิทธิ์สีลคุณ; สองเมือง, ณัฏฐ์พิชญา; แสนสิ่ง, พีรพงษ์ (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
This research aimed to study the level of word pronunciation in Thai and to compare the learning achievement in developing Thai word pronunciation skills among Mathayomsuksa 1 (Grade 7) students at Srithamwittaya School, Nai Mueang Subdistrict, Mueang District, Yasothon Province. The target group consisted of 50 Mathayomsuksa 1 students in the first semester of the 2024 academic year. This study employed a quasi-experimental research design. The results showed that the level of Thai word pronunciation and the learning achievement in developing word pronunciation skills among Mathayomsuksa 1 students in the first semester of the 2024 academic year at Srithamwittaya School were at a moderate level (m = 3.03, s = 0.79). Furthermore, the comparison of learning achievement in developing Thai word pronunciation skills revealed that students' ability to pronounce difficult words was also at a moderate level (m = 3.03, s = 0.79), which meets the 80/80 criterion.